RANCANG BANGUN MANAJEMEN PERTEMUAN TINGKAT ESELON I DI KEMENTERIAN KESEHATAN BERBASIS WEB - Dodi Angga Kusuma; Kemal Nazaruddin Siregar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Online meetings have become mandatory since the COVID-19 pandemic. The series of stages of online meetings are slightly different from those held offline. Using the online meeting application requires a license and meeting scheduling according to the license quota you have. Online meeting activities at the Ministry of Health, especially the work unit under the Secretary General, provide each online meeting application license, and the meeting management is still manual. The stages of the meeting which include ordering meeting schedules, sending meeting invitations to participants, making minutes and approval from the leadership, distributing minutes to meeting participants are still done manually, and also not yet integrated with offline meeting activities. This condition is not cost effective and time efficient. The purpose of this research is to design and develop an application web-based information system for online meetings and minutes within the Ministry of Health. The designed information system is the Echelon I Level Meeting Management Information System. The system development method used is the System Development Life Cycle (SDLC) with a prototype approach. The system design uses the PHP programming language, and also uses MySQL to design the database. The conceptual design is in accordance with the results of the analysis of existing conditions and is used as a reference in designing web-based information systems including using data flow diagrams, entity relationship diagrams, and table relationship diagrams. The results of this study are in the form of an integrated information system for work units at the Ministry of Health in managing online and offline meetings, integrating meeting room reservations (if online in the form of reservations for online meeting application slots such as zoom), automation of sending invitations to all meeting participants, making minutes online meeting and its approval, as well as sending the minutes of the meeting through the system. The advantages of this information system include saving costs for procuring online application licenses, generating a database of all meeting activities at the Ministry of Health, automation of sending invitations and meeting minutes, time efficiency in following up on meeting results because minutes can be made directly online and sent via the system to all meeting participants.